Evaluating the Seismic Resilience of Newly Constructed Concrete Building in Zinda Jan District After the Devastating October 2023 Earthquake in Herat, Afghanistan - Alkozay, Arif; Rahimullah Stankzai; Amanollah Faqiri (International Journal of Integrated Science and Technology, 2024)
This study aims to evaluate the impact of the October 2023 earthquake on the Zinda Jan district, focusing on the structural integrity of more than 2000 newly constructed buildings situated near fault lines. The specific objective is to identify any vulnerabilities in the design of these structures. Advanced computer analyses, including Linear and Non-linear (Push-over analysis) assessments using Etabs software, were employed to investigate the structural performance of the buildings. The analysis revealed significant insights into the structural integrity of the new constructions. It was observed that certain central columns exhibited inadequate strength, thereby posing a considerable risk of failure during seismic events. This vulnerability primarily stems from a disparity in strength between columns and beams, with the latter being stronger. This research contributes to the field by emphasizing the critical role of meticulous design and analysis in safeguarding buildings located in earthquake-prone regions.